2008
DOI: 10.1007/s00392-008-0735-9
|View full text |Cite
|
Sign up to set email alerts
|

TIMI 3 flow after primary angioplasty is an important predictor for outcome in patients with acute myocardial infarction

Abstract: BackgroundGrowing evidence suggests that poor coronary blood flow after primary percutaneous coronary intervention (PCI) is associated with unfavorable clinical out-come. We retrospectively evaluated data from our single center “real world patients” database of patients undergoing primary PCI to determine differences in clinical and angiographic patterns in patients with or without restoring thrombolysis in myocardial infarction (TIMI) flow 3.Methods and resultsBetween 2001 and 2006, 500 patients underwent pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 24 publications
4
37
0
Order By: Relevance
“…A few studies showed that TIMI-3 flow before PCI was an independent determinant of survival in AMI treated by primary PCI [4,5]. The post-procedural TIMI flow grade <3 has also been reported to be a risk factor of an early and late mortality in AMI [9]. Mehta et al showed that unsuccessful PCI, defined by TIMI < 3 after PCI, in STEMI patients with cardiogenic shock was associated with significantly higher in-hospital mortality rates [10].…”
Section: Discussionmentioning
confidence: 97%
“…A few studies showed that TIMI-3 flow before PCI was an independent determinant of survival in AMI treated by primary PCI [4,5]. The post-procedural TIMI flow grade <3 has also been reported to be a risk factor of an early and late mortality in AMI [9]. Mehta et al showed that unsuccessful PCI, defined by TIMI < 3 after PCI, in STEMI patients with cardiogenic shock was associated with significantly higher in-hospital mortality rates [10].…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, Duran et al showed that high levels of UA affect the coronary collateral vessels (CCV) development negatively in patients with ACS [19]. We know that poor coronary blood flow following primary PCI and undeveloped CCV related closely in prognosis patients with MI [20,21].…”
Section: To the Editormentioning
confidence: 95%
“…The clinical practice in PCI procedures focuses on restoration of epicardial blood flow, as patients with optimal blood flow in culprit vessel after PCI for acute myocardial infarction (AMI) have less extensive necrosis and better regional and global contractile function, lower incidence of adverse events and mortality than patients with poor postprocedural blood flow in infarct-related artery 1,2 . The success rate of achieving the postprocedural TIMI 3 flow and related patient characteristics in the present study conform to other studies: patients with postprocedural TIMI <3 flow were older, more commonly women, diabetics, with more frequent initial hemodynamic instability (Table 1) (ref.…”
Section: Timi-3 Flow As An Outcome Predictormentioning
confidence: 99%
“…Restoration of epicardial blood flow in the infarctrelated artery (IRA) in patients with myocardial infarction is associated with greater myocardial salvage and increased survival 1,2 . The patency rate of the IRA in STEMI patients treated with fibrinolysis ranges between 60% and 80% and is strongly time-dependent [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%